Gender Equality, Infrastructure and PPPs : A Primer - World Bank (Washington, DC, 2022)
For all of our age’s technological advances, service innovations, and instant connectivity, gender inequality stubbornly remains a defining characteristic of the structure of our economies and the opportunities for our citizens. This is especially true in many corners of the developing world, where women trail men in health and educational outcomes, access to jobs and assets, and their ability to voice their opinions and exercise agency over their lives. Urban transit systems that are mapped against job locations for women, designed to provide security, and operated to remove uncertainty of arrival times, are essential to balancing labor opportunities for female workers. In the various infrastructure sectors, the authors are pleased to report that best-practice examples have been mounting. Yet, for infrastructure-development professionals, particularly those focused on crowding in private financing and operations and preparing public-private partnerships (PPPs), knowing where to start integrating gender equality concerns into our work can be daunting. However daunting, the incorporation of gender considerations is uniquely important for PPPs, where private-service providers become the main interface with consumers. This report consolidates and draws from a wide spectrum of examples that cut across sectors to demonstrate how infrastructure, its development, and the policies and regulations governing its construction and operation, can play a role in closing gaps between women and men. It pinpoints approaches for ensuring that projects not only do no harm, but also serve as vehicles for empowerment, providing practical guidance that can be systematically integrated into PPP projects and frameworks. The primer points out that best practices at the intersection of gender equality and infrastructure PPPs are still evolving.